Modeling and experimentally characterizing ionic buoyancy engines - Akle, Barbar J. (2017)
There is a need for buoyancy engines to modulate sensor depth for optimal positioning and station-keeping. Compared to current technologies, Ionic Buoyancy Engines does not have any moving parts. They are energy efficient and miniaturization ready. Ionic Buoyancy Engines change their density by locally varying ionic concentrations in a closed chamber with a wall made of a semi-permeable membrane. The local change in concentration pumps water in and out of the chamber leading to buoyancy change. This study presents a model that is used to simulate the steady state controlled depth of the buoyancy engine, along with experimental results.